PERAN GEREJA DALAM MENINGKATKAN MOTIVASI UNTUK BERIBADAH SECARA TATAP MUKA PASCA PANDEMI COVID - Martinus Hartono Sodikdiana; Yanto Paulus Hermanto; Christopher Santoso (Phronesis: Jurnal Teologi dan Misi, 2023)
After two years of a pandemic where worship activities could not be carried out and were limited, the government began to relax the rules for worship, and churches resumed their activities and held face-to-face worship. Even though some congregations are starting to come to worship face-to-face enthusiastically, others are still choosing to worship online. During the hybrid worship period, where online services are still held simultaneously as face-to-face services, the church seeks various ways to invite the entire congregation back to attend services. Based on direct observations and interviews with pastors and congregations that have attended, various factors have been found that can be a driving force for congregations longing to attend face-to-face activities; the church also uses various creative ways to provoke the desire of congregations that are not present to be able to feel and remember the enjoyment worship directly. Efforts to attract the congregation to return to attendance, thanks to the role of the pastor's attention to the congregation and various supporting factors, have resulted in the return of almost the entire congregation for face-to-face worship.